2020
DOI: 10.1177/0194599820912727
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Complications of Osteocutaneous Free Flaps in Head and Neck Reconstruction

Abstract: Objective To determine the frequency at which patients with osteocutaneous free flap reconstruction of the head and neck develop long-term complications and identify predisposing perioperative factors. Study Design A prospectively maintained database of free flaps performed at a single institution over a 10-year period was queried. Setting Single tertiary care referral center. Subjects and Methods In total, 250 osseous or osteocutaneous free flaps (OCFFs) for mandibular or maxillary reconstruction were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(63 citation statements)
references
References 22 publications
(72 reference statements)
2
50
0
1
Order By: Relevance
“…The main morbidity associated with FFF is difficulty with wound healing and paresthesias; however, some authors have reported gait disturbances and motor weakness 3,7 . Despite some limitations, there are relatively few long‐term complications given that the fibula is a non–weight‐bearing bone of the lower extremity 1,3,4 …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The main morbidity associated with FFF is difficulty with wound healing and paresthesias; however, some authors have reported gait disturbances and motor weakness 3,7 . Despite some limitations, there are relatively few long‐term complications given that the fibula is a non–weight‐bearing bone of the lower extremity 1,3,4 …”
Section: Introductionmentioning
confidence: 99%
“…Given the prevalence of knee replacement, it is not uncommon for the head and neck surgeon to encounter a patient with prior TKA during preoperative evaluation. In some instances, when a FFF is not possible due to prior trauma or peripheral vascular disease, most surgeons will turn to the osteocutaneous radial forearm (OCRFF) or scapular free flap 1,10 . A few have also harvested the anterolateral thigh osteocutaneous flap (ALTO) 11 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations